The Influence of Stress and Resilience on Procrastination in Adolescents - Hernisawati, Hernisawati; Khasanah, Uswatun; Maba, Aprezo Pardodi (Bulletin of Counseling and Psychotherapy, 2022)
Procrastination in adolescents does not happen immediately like me, there are several factors that trigger procrastination, including stress and resilience. This study aims to find out whether stress and resilience have an influence on procrastination. The type of research in this research is quantitative using a descriptive research design. The results of the study stated that stress and resilience can affect procrastination by 4.8%, which means that these two variables have very little effect on procrastination. While the significance value is 0.60 > 0.05, which means it is not significant. Specifically, there is a low negative correlation between stress and resilience (r = -0.017), meaning that the higher the individual's resilience, the lower the stress level. There is a strong positive correlation between stress and procrastination (r = 0.202), meaning that the higher the individual's stress level, the higher the procrastination. In addition, procrastination was found to have a small positive correlation with resilience (r = 0.081), meaning that high resilience in individuals can make individuals procrastinate, but with a small percentage. It can be concluded that there is an insignificant effect between stress and resilience on procrastination, which is 4.8% which tends to be small.